IMPORTANT DIRECTIONS FOR THE DEVELOPMENT OF ECOLOGICAL TOURISM IN THE CONTEXT OF NEW UZBEKISTAN - Khamrayev Sardorbek Sharafutdinovich (Western European Studies, 2025)
This article explores the key directions for developing ecological tourism in the context of New Uzbekistan. It highlights the importance of preserving natural ecosystems while promoting sustainable tourism practices. The study analyzes the current state of ecotourism in the country, the potential for growth, and strategic measures needed for further development. The role of environmental awareness, infrastructure improvement, and government support are emphasized as critical factors in fostering eco-tourism in Uzbekistan's new era of reform and modernization
Keywords: Ecological tourism; sustainable development